Ausweis, Exil, Flucht und Migration - Patrice Djoufack (Recherches Germaniques, 2018)
What does an identity card mean to a refugee who is seeking asylum? Drawing on the story of the ancient protection-seeking Danaids, Julia Kristeva developed the conception that we are strangers to ourselves, whereby the stranger proves to be, uncannily, part of our own identity. To grant a stranger political asylum means, in this understanding, the same thing as to offer hospitality to a member of the tribe. Analyzing modern migration processes, this paper casts a critical eye at this conception. Based on the literary production of selected German writers, who experienced exile during national socialism, and first and foremost, on Anna Seghers’ novel Transit, the paper illustrates to what extent the possession of a valid identity card can be said to have an existential value to refugees in modern times. Faking such a document therefore appears as a survival strategy by means of which refugees manage to get by as they are faced with a state apparatus intent on maintaining order, lacking humanity and subjecting them to perpetual police harassment. Against this background, the paper questions the possibility of a more humane treatment of refugees and points at the new risks which could be connected to such a treatment.